Blended Learning Models Using Moodle Spada UNRAM To Improve Student Learning Outcomes In Religious Education Subjects - Rispawati, Rispawati; Fauzan, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to determine the application of the blended learning model using Spada Unram's Moodle so that it is expected to improve student learning outcomes in religious education courses in the PPKn Study Program FKIP University of Mataram. Seeing the conditions of the Covid-19 pandemic that have not yet ended, lecturers need to find learning innovations based on a combination of online and offline using Moodle Spada Unram so that learning for students can be effective and efficient. This type of research is quasi-experimental. The results of the study are as follows: 1) this study shows that the application of the blended learning model using the SPADA UNRAM Moodle in religious education subjects can provide positive changes in learning outcomes; 2) Make it easy for students to collaborate so they can develop their ideas well; 3) Students can access and download teaching materials in PDF or PPT format through Moodle SPADA as literacy enrichment related to religious education courses. 4) applying the blended learning model using the SPADA UNRAM Moodle, which is collaborative or work between groups in the implementation process. Not only does the lecturer appear active, but students can explore material, discuss with groups, express opinions and discuss. Lecturers help direct students in concluding material, so variations in learning and student involvement in lectures appear by themselves.